Study on the effect of Ca content in 4n Gold Wire for Qfn Stacked Die Package - Azman, Jalar; Saidatul Azura, Radzi; M.A. A., Hamid (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.